War and Technology - Black, Jeremy M. (Book collections on Project MUSE., 2013)
In this book, the author argues that technology neither acts as an independent variable nor operates without major limitations. This includes its capacity to obtain end results, as technology's impact is far from simple and its pathways are by no means clear. After considering such key conceptual points, the author discusses important technological advances in weaponry and power projection from sailing warships to aircraft carriers, muskets to tanks, balloons to unmanned drones - in each case, taking into account what difference these advances made. He addresses not only firepower but also power projection and technologies of logistics, command, and control. Examining military technologies in their historical context and the present centered on the Revolution in Military Affairs and Military Transformation, the author then forecasts possible future trends.